Effectiveness of a Mathematics Instructional Package on PÃ³lyaâ€™s Steps Including Video Clips to Enhance Problem Solving Abilities of 6th Grade Students in Bhutan - Namgyal, Tenzin; Kongmanus, Kobsook (International Journal of Engineering and Technology, 2018)
This study investigated three objectives: 1) to determine the effectiveness of a mathematics instructional package on Ployaâ€™s steps including video clips to enhance problem solving abilities of 6th grade students in Bhutan, 2) to compare studentsâ€™ mathematics problem-solving abilities before and after implementing the package by using a pretest and posttest, and 3) to examine studentsâ€™ satisfaction level after learning with the mathematics instructional package. In the first semester of 2017, twenty-eight 6th grade students at Khamdang Lower Secondary School in Trashi Yangtse District in Bhutan were selected as the sample by employing the purposive sampling technique. The instruments used in this study were 1) the instructional package (lesson plans on PÃ³lyaâ€™s steps with video clips), 2) problem-solving ability tests, and 3) questionnaires. The data were statistically analyzed to determine the effectiveness index (E.I), dependent sample t-test, mean and standard deviation. The results revealed that the effectiveness index of the lesson plans of the instructional package was higher than the set criteria of 0.50. The improvements in problem solving abilities of the students after implementing the instructional package were statistically significant (p<0.05). The studentsâ€™ satisfaction level after implementation of the instructional package proved to be â€œvery highâ€. In conclusion, the lesson plans on PÃ³lyaâ€™s steps including video clips were determined to be an effective tool to increase 6th grade studentsâ€™ mathematics problem-solving abilities.Â Â Â Â